Exploration and characterisation of the phenotypic and genetic profiles of patients with early onset schizophrenia associated with autism spectrum disorder and their first-degree relatives: a French multicentre case series study protocol (GenAuDiss). Issue 7 (5th July 2018) - Fernandez, Arnaud; Dor, Emmanuelle; Maurin, Thomas; Laure, Gaelle; Menard, Marie-Line; Drozd, Małgorzata; Poinso, Francois; Bardoni, Barbara; Askenazy, Florence; Thümmler, Susanne
Abstract : Introduction: Early-onset schizophrenia (EOS) is a rare and severe condition. A higher rate of neurodevelopmental abnormalities, such as intellectual or communication impairments as well as attention deficit hyperactivity disorder, is observed in EOS compared with adult-onset schizophrenia. Early signs of autism spectrum disorders (ASD) are present in about 30% of patients. Genetic abnormalities, including copy number variations, are frequent in neurodevelopmental disorders and have been associated to ASD physiopathology. Implicated genes encode proteins involved in brain development, synapses morphology and plasticity and neurogenesis. In addition, an increasing number of genetic abnormalities are shared by EOS and ASD, underlying the neurodevelopmental hypothesis of EOS. The main objective of our study is to identify disease-causing genetic mutations in a cohort of patients affected by both EOS and ASD. Special attention will be paid to genes involved in neurodevelopmental pathways. Methods and analysis: We describe a multicentric study in a paediatric population. The study started in April 2014. Inclusion criteria are: age 7–22 years, diagnosis of EOS with comorbid ASD and IQ >50; Parents and siblings are also enrolled. We perform psychiatric assessments (Mini International Neuropsychiatric Interview, Kiddie Schedule for Affective Disorders and Schizophrenia -Present and Lifetime Version, Positive and Negative Syndrome Scale and Scale for the Assessment of Negative Symptoms) together with neurocognitive evaluations (IQ, Trail Making Test A/B and verbal fluency). Then, we study variants of the coding part of DNA (exome), using next-generation sequencing process on trio (mother, father and child). Bioinformatics tools (RVIS and PolyPhen-2) are used to prioritise disease-causing mutations in candidate genes. The inclusion period will end in November 2019. Ethics and dissemination: The study protocol was approved by the Local Ethic Committee and by the French National Agency for Medicines and Health Products Safety. All patients signed informed consent on enrolment in the study. Results of the present study should help to unravel the molecular pathology of EOS, paving the way for an early therapeutic intervention. Trial registration number: NCT0256552; Pre-results.